Answer:
d is the answer
Step-by-step explanation:
Answer:
Factoring the trinomial:
we get the factors ![\mathbf{(x+1)(x+12)}](https://tex.z-dn.net/?f=%5Cmathbf%7B%28x%2B1%29%28x%2B12%29%7D)
Step-by-step explanation:
We need to factor the trinomial: ![x^2+13x+12](https://tex.z-dn.net/?f=x%5E2%2B13x%2B12)
We can factor the trinomial by breaking the middle term i.e 13x
Such that adding or subtracting gets the both terms we get 13x and multiplying both terms we get 12x^2
We can break 13x as: 12x and x
Adding them we get 13x and multiplying them we get 12x^2
So,
![x^2+13x+12\\=x^2+12x+x+12\\=x(x+12)+1(x+12)\\=(x+1)(x+12)](https://tex.z-dn.net/?f=x%5E2%2B13x%2B12%5C%5C%3Dx%5E2%2B12x%2Bx%2B12%5C%5C%3Dx%28x%2B12%29%2B1%28x%2B12%29%5C%5C%3D%28x%2B1%29%28x%2B12%29)
So, Factoring the trinomial:
we get the factors ![\mathbf{(x+1)(x+12)}](https://tex.z-dn.net/?f=%5Cmathbf%7B%28x%2B1%29%28x%2B12%29%7D)
Answer:
1.5/6
2.1/6
Step-by-step explanation:
O is the midpoint of Reason: Defintiin of a midpoint